Pengaruh Kepemilikan Manajerial, Women CEO dan Water Accounting Terhadap Manajemen Laba - Siti Fazriani; Dirvi Surya Abbas; Ahmad Zaki (MUQADDIMAH: Jurnal Ekonomi, Manajemen, Akuntansi dan Bisnis, 2024)
The purpose of this study is to determine the influence of managerial ownership, women ceo and water accounting on profit management in Manufacturing Companies listed on the IDX in 2019-2021. This study used quantitative proximity. The population in this study is Manufacturing Companies on the Indonesia Stock Exchange in 2019-2021, which is 787 companies. The sampling technique used was purposive sampling and a sample of 21 companies was obtained. The data analysis technique used is panel data regression with Eviews software version 9. The results showed that there is no effect of managerial ownership on profit management. There is an influence of women CEOs on profit management. There is an effect of water accounting on profit management.